2020
DOI: 10.1136/tsaco-2020-000557
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons in surge — the versatility of the acute care surgeon: outcomes of COVID-19 ICU patients in a community hospital where all ICU patients are managed by surgical intensivists

Abstract: BackgroundReported characteristics and outcomes of critically ill patients with COVID-19 admitted to the intensive care unit (ICU) are widely disparate with varying mortality rates. No literature describes outcomes in ICU patients with COVID-19 managed by an acute care surgery (ACS) division. Our ACS division manages all ICU patients at a community hospital in New Jersey. When that hospital was overwhelmed and in crisis secondary to COVID-19, we sought to describe outcomes for all patients with COVID-19 admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Natural disasters such as landslides, tornadoes, earthquakes, and tsunamis are a type of MCI where more than 100,000 people are killed around the world and millions more are injured or disabled each year. 8 , 9 Unfortunately, in most natural disasters, people have either minimal or no time to prepare or seek shelter during these, contributing to the severity of the MCI. Other contributing factors that must be accounted for is the widespread destruction that can affect hospitals and emergency response teams that impairs their ability to respond.…”
Section: Types Of Events Causing Mass Casualty Incidentsmentioning
confidence: 99%
“…Natural disasters such as landslides, tornadoes, earthquakes, and tsunamis are a type of MCI where more than 100,000 people are killed around the world and millions more are injured or disabled each year. 8 , 9 Unfortunately, in most natural disasters, people have either minimal or no time to prepare or seek shelter during these, contributing to the severity of the MCI. Other contributing factors that must be accounted for is the widespread destruction that can affect hospitals and emergency response teams that impairs their ability to respond.…”
Section: Types Of Events Causing Mass Casualty Incidentsmentioning
confidence: 99%
“…The versatility of SCC physicians in providing trauma triage, initial stabilization, operative intervention, and subsequent critical care grants hospitals a ready-to-deploy team while preserving continuity of care and redundancy in operations. Lessons from military combat have been integrated into routine trauma training, bringing adaptability in extraordinary circumstances and experience with resource distribution in environments of scarcity, making SCC providers particularly prepared to lead during crises 74,75 …”
Section: Disaster and Pandemic Carementioning
confidence: 99%
“…Lessons from military combat have been integrated into routine trauma training, bringing adaptability in extraordinary circumstances and experience with resource distribution in environments of scarcity, making SCC providers particularly prepared to lead during crises. 74,75 The COVID-19 pandemic has brought glaring visibility to the necessity of hospitals and health systems to maintain flexibility and built-in safety systems to navigate through crises. While blunt trauma volumes decreased noticeably during the pandemic, penetrating trauma rates and proportions increased.…”
Section: Disaster and Pandemic Carementioning
confidence: 99%
“…Lack of earlier diagnosis and screening for disease and routine follow-up may be the major reason that causes the severity of disease during the pandemic period[ 11 ]. Moreover, one study reported that an acute care surgery division is able to manage the intensive care for COVID-19 patients independent of surgical procedures[ 12 ].…”
Section: To the Editormentioning
confidence: 99%